Global Climate Change and Response: Analysis from Sociological Perspectives - Acharya, Nabin (Journal of Development Review, 2023)
Climate change is one of the greatest challenges of the contemporary world. From the beginning, natural sciences within the specific discipline have dominated climate change research and have been successful in identifying the relationship between human action and environmental change but are unable to see the relationship within society that builds environmentally damaging social structure. Sociologists have made important contributions in identifying the effects of social structure on greenhouse gas (GHG) emissions. Sociology provides a wealth of resources including different concepts and theories that take into account the influence of social norms, values, cultural beliefs, power, social inequalities, vulnerabilities, and global systems in causing climate change. This paper is based on the review of different articles, book chapters and research reports related to climate change and examine the causes, impacts and response measures from sociological perspectives and insights. The study showed that the individual’s consumption behaviour that drives GHG emissions is constrained by the contexts of the society and the working of the global system. The impacts of climate change are varied among social groups and societies so need to take account the underlying causes of social inequalities, vulnerabilities and climate injustice at both national and global levels. The paper concludes that without understanding the complex interaction between individuals and the socio-cultural, economic and political context of the society we cannot deal with the current challenges of climate change.